Socio-demographic characteristics of parents and emotional burden on discovery of disabilities of their children in a South African community - U. Useh (AOSIS, 2008)
Objective: This study investigated the socio-demographic characteristicsof parents of children with disabilities in a South African community. Also studiedwere their emotional responses. Design and methodology: A social survey research and focus group designs wereemployed in this study to explore and describe parental emotions Participants: 174 parents of children with disabilities were randomly selected andinterviewed by this author and four research assistants at different locations in theVenda area of Limpopo Province of South Africa. Results: Out of the 174 parents interviewed 95 (54.6%) were parents of children with physical impairment (PCWPI),51 (29.3%) parents of children with hearing impairment (PCWHI) and 28 (16.1%) were parents of children with visual impairment (PCWVI).  Only 16 (9.2%) of the parents interviewed had tertiary education with a majority (121 (or 69.5%) of them unemployed. These unemployed parents solely relied on the monthly, government disabilitygrant of R620 (or US$89). Responses to grief, anger, shame were highest amongst PCWVI, while PCWPI were most worried (64.2%) and demonstrated the highest percentage emotions of fear (22.1%) and guilt (221.1%). The following percentage of emotions were expresses by parents with formal tertiary education, anger (44%), shame (37.5%), disbelief (25%), guilt (6.3%), worry (50%) and fear (25%). While participants with the highest income (over R1800or about US$257), expressed the following percentage of emotions: grief (70.6%), and disbelief (47.1%). Conclusion: Physiotherapist working with the disabled and their carers in the community within the concept of community based rehabilitation and social model of care would need to understand the characteristics and their emotional burden prior to assisting in creating an enabling environment and holistic empowering activities that wouldassist all.